The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1051/0004-6361/201118575
|View full text |Cite
|
Sign up to set email alerts
|

Multi-line detection of O2towardρOphiuchi A

Abstract: Context. Models of pure gas-phase chemistry in well-shielded regions of molecular clouds predict relatively high levels of molecular oxygen, O 2 , and water, H 2 O. These high abundances imply high cooling rates, leading to relatively short timescales for the evolution of gravitationally unstable dense cores, forming stars and planets. Contrary to expectations, the dedicated space missions SWAS and Odin typically found only very small amounts of water vapour and essentially no O 2 in the dense star-forming int… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 50 publications
(50 reference statements)
5
68
1
Order By: Relevance
“…But owing to the high sensitivity of this survey, one could have hoped to detect some of those species already known elsewhere in the interstellar medium, in comets, or mysteriously absent such as the first two we discuss now. (Goldsmith et al 2000) and Odin (Pagani et al 2003) spacecrafts, counterbalanced by a single detection in ρ Ophiuchi (Larsson et al 2007) with Odin, we detected O 2 towards Orion (Goldsmith et al 2011) and confirmed the detection towards ρ Ophiuchi, (Liseau et al 2012). However, the location of the emission in Orion is ill-defined and that made the interpretation of the observations difficult (Goldsmith et al 2011;Chen et al 2014;Melnick & Kaufman 2015).…”
Section: Non-detection Of Species In Orionsupporting
confidence: 73%
“…But owing to the high sensitivity of this survey, one could have hoped to detect some of those species already known elsewhere in the interstellar medium, in comets, or mysteriously absent such as the first two we discuss now. (Goldsmith et al 2000) and Odin (Pagani et al 2003) spacecrafts, counterbalanced by a single detection in ρ Ophiuchi (Larsson et al 2007) with Odin, we detected O 2 towards Orion (Goldsmith et al 2011) and confirmed the detection towards ρ Ophiuchi, (Liseau et al 2012). However, the location of the emission in Orion is ill-defined and that made the interpretation of the observations difficult (Goldsmith et al 2011;Chen et al 2014;Melnick & Kaufman 2015).…”
Section: Non-detection Of Species In Orionsupporting
confidence: 73%
“…The success story of combined laboratory and observational studies became complete with the detection of gas-phase HO 2 199 Interestingly, ρ Oph A is also one of only two positions where interstellar O 2 gas has been firmly detected through multi-line observations with the Odin and Herschel satellites 202,203 . Deep limits in other cold cores confirm the scenario in which most of the O and O 2 must be converted into H 2 O ice on the grains before the protostar starts to heat its surroundings 204,205 .…”
Section: H 2 O O 2 and The Importance Of Solid-state Chemistrymentioning
confidence: 99%
“…Goldsmith et al 2000;Pagani et al 2003), with the definite detection of the molecule in merely two sources, viz. ρ Oph A (Larsson et al 2007;Liseau et al 2012) and Orion A (Goldsmith et al 2011;Chen et al 2014). Some cases have been either resolved or remained undecided (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al (2014) were able to pinpoint the location of the 9 O 2 source, near the position identified as H 2 -Peak 1 and somewhat offset from the hot core centre. The non-detection of the O 2 line at 1121 GHz led the authors to conclude that gas temperatures do not exceed 50 K, with best-fit model values more like 30 K. The excitation conditions thus resemble those in ρ Oph A (Liseau et al 2012). Du et al (2012) developed models for grain surface chemistry, and as an example, they considered the particular case of ρ Oph A.…”
Section: Introductionmentioning
confidence: 99%